Difference in the Seawater Tolerance of Anadromous and Landlocked Populations of Arctic Char ( Salvelinus alpinus ) - Staurnes, Magne; Sigholt, Trygve; Lysfjord, Grete; Gulseth, Odd A. (Canadian Journal of Fisheries and Aquatic Sciences, 1992)
The seawater tolerance of juvenile fish from an anadromous and a landlocked population of Arctic char (Salvelinus alpinus), reared in freshwater under a constant light regime, was compared by making repeated seawater challenge tests from one summer to the next. Fish from the landlocked population had higher mortality rates and higher blood plasma Na + concentrations after transfer to seawater than those from the anadromous population. The gill Na-K-ATPase activity of the landlocked fish was lower than that of the anadromous fish. For both populations, the smallest fish showed the lowest seawater tolerance, but hypoosmoregulatory ability was independent of fish size for fish larger than about 60 g. By June of the second summer, fish from the anadromous, but not those from the landlocked population, developed seawater tolerance 10 d after transfer to seawater. This increase in hypoosmoregulatory ability was accompanied by a doubling of the gill Na-K-ATPase activity.